2015
DOI: 10.3892/ijo.2015.2928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fucoidan on proliferation, AMP-activated protein kinase, and downstream metabolism- and cell cycle-associated molecules in poorly differentiated human hepatoma HLF cells

Abstract: Survival rates are low in patients with poorly differentiated hepatocellular carcinoma (HCC). Fucoidan, a sulfated polysaccharide derived from brown seaweed, has anticancer activity; however, the effects of fucoidan on poorly differentiated HCC remain unclear. In this study, we investigated the effects of fucoidan on AMP-activated protein kinase (AMPK), a proliferation regulator, and its downstream metabolism- and cell cycle-related molecules in a poorly differentiated human hepatoma HLF cell line. HLF cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…The results of the present study demonstrated that the protein level of p27 was increased in CMTM7‐overexpressed cells, which led to the further inhibition of cell cycle progression. In addition, AMP‐activated protein kinase (AMPK) has also been reported to be involved in the cell growth of liver cancer cells via regulation of cyclin D1, CDK4, and CDK6 . However, whether CMTM7 regulates AMPK was not examined in the present study, and these experiments will be performed in our future work.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The results of the present study demonstrated that the protein level of p27 was increased in CMTM7‐overexpressed cells, which led to the further inhibition of cell cycle progression. In addition, AMP‐activated protein kinase (AMPK) has also been reported to be involved in the cell growth of liver cancer cells via regulation of cyclin D1, CDK4, and CDK6 . However, whether CMTM7 regulates AMPK was not examined in the present study, and these experiments will be performed in our future work.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, AMP-activated protein kinase (AMPK) has also been reported to be involved in the cell growth of liver cancer cells via regulation of cyclin D1, CDK4, and CDK6. 28 However, whether CMTM7 regulates AMPK was not examined in the present study, and these experiments will be performed in our future work.…”
Section: Discussionmentioning
confidence: 94%
“…24 Fucoidan significantly blocks the proliferation of human hepatoma HLF cells, a poorly differentiated HCC cell line, and maintains the cell cycle in the G1/S phase. 2 Hence, the hypothesis of the present study is that fucoidan can induce apoptosis and inhibit the proliferation of HCC cells via modulation of the p38 MAPK/ERK and PI3K/Akt pathways. Here, a mouse xenograft tumor model was used to assess the potential of fucoidan as an adjuvant therapeutic agent against HCC.…”
Section: Introductionmentioning
confidence: 86%
“…Fucoidan is a fucose-rich sulfated carbohydrate derived from brown seaweed, that possesses anti-oxidant, anti-viral, anti-angiogenic, anti-inflammatory, antiproliferative, and anti-bacterial properties as well as anticancer activities against various tumors, especially those of the digestive system. [1][2][3][4][5] The mechanisms underlying the anticancer activities of fucoidan may be related to the targeting of multiple signaling molecules and receptors of various cells, including immune and tumor cells, which could directly induce apoptosis and cytotoxicity of cancer cells. 6 According to recent global cancer statistics, hepatocellular carcinoma (HCC) remains the most common malignancy of the liver.…”
Section: Introductionmentioning
confidence: 99%
“…AMP-activated protein kinase (AMPK) is a highly conserved heterotrimeric kinase complex. Activation of AMPK leads to the inhibition of mTORC1 via a tuberous sclerosis complex 2 (TSC2)-dependent or -independent mechanism (6). In animal models with impaired mTORC1 signaling, AMPK is highly activated (7), suggesting a negative crosstalk between these two pathways.…”
Section: Introductionmentioning
confidence: 99%